Risks, rewards and regulation of unconventional gas, by R. Quentin Grafton, Ian G. Cronshaw and Michal C. Moore, 2017. Cambridge University Press, Cambridge. 509 pages. Hardback:. price £71.99, ISBN 9781107120082. - Duczmal-Czernikiewicz, Agata (Geologos, 2018)
[Missing]